(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2021)
The rise of the Second Apostolic Age brought about the emergence of numerous opportunities which enable the miracle-oriented individuals to connect to the spirit realm. The so-called power portals are believed to be highly influential, especially within the neo-Charismatic communities. The disciples of Peter C. Wagner, an American missionary who restored the apostolic model of leadership, appear to perceive graves as the wondrous channels between a human being and the supernatural. For the last few years, the students of Bethel School of Supernatural Ministry (BSSM) from Redding in California have been practicing necromancy in the form of magical contagion, also known as grave soaking, grave sucking or mantle grabbing, which consists in soaking up the spiritual power of the deceased. The principal objective is to analyze whether the above-mentioned ritual, performed by the convinced Christians, is somehow related to magical behavior. Moreover, this particular research focuses on the proper understanding of how the law of contagion has been implemented into the activities undertaken by Bethel’s students. The first part of the article emphasizes the main characteristics of the New Apostolic Reformation. The second part concentrates on the concepts such as the divine anointing and impartation, whereas the third one applies to a specific case of necromancy.